2015
DOI: 10.1182/blood-2014-08-595561
|View full text |Cite
|
Sign up to set email alerts
|

Programmable 3D silk bone marrow niche for platelet generation ex vivo and modeling of megakaryopoiesis pathologies

Abstract: Key Points Natural silk protein sponge and vascular tubes reproduce human bone marrow niche environments for functional platelet generation ex vivo. Programmable bioengineered model for the investigation and therapeutic targeting of altered platelet formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
189
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(198 citation statements)
references
References 60 publications
3
189
0
6
Order By: Relevance
“…The second, dedicated to the implementation of this knowledge into our recently established silk-based bone marrow model, integrates important physical and physiological elements characterizing the hematopoietic niche, conducive to evaluating platelet production. 22 Together our studies demonstrate that eltrombopag significantly increases the activation of all the major c-Mpl downstream signaling pathways in a dose-dependent manner, and that this is paralleled by the differentiation of human HSCs, which results in an increased output of mature megakaryocytes which show an improved ability to form proplatelets and release platelets. Furthermore, we propose a novel mechanism explaining such effects on thrombopoiesis through the activation of AKT and ERK1/2 signaling molecules.…”
Section: Introductionmentioning
confidence: 82%
“…The second, dedicated to the implementation of this knowledge into our recently established silk-based bone marrow model, integrates important physical and physiological elements characterizing the hematopoietic niche, conducive to evaluating platelet production. 22 Together our studies demonstrate that eltrombopag significantly increases the activation of all the major c-Mpl downstream signaling pathways in a dose-dependent manner, and that this is paralleled by the differentiation of human HSCs, which results in an increased output of mature megakaryocytes which show an improved ability to form proplatelets and release platelets. Furthermore, we propose a novel mechanism explaining such effects on thrombopoiesis through the activation of AKT and ERK1/2 signaling molecules.…”
Section: Introductionmentioning
confidence: 82%
“…Maximising platelet production in vitro from these MKs will be a condition without which production of platelets on the scale necessary for a clinically relevant product (each platelet concentrate contains 3 × 10 11 platelets) will remain a dream. The apparent shortfall in platelet formation might be due to our inability to re-create the niche signal (including shear) necessary for efficient proplatelet formation and platelet release, although several approaches using 3D bioreactors have been published to that effect [212][213][214]. It is also worth mentioning that the evidence that platelets released in vitro are functional has been gathered using descriptive rather than quantitative assays with usually no comparison to platelets freshly isolated from donors.…”
Section: Harvesting Platelets From In Vitro-produced Mksmentioning
confidence: 99%
“…9 Moreover, the development of techniques for culturing Mks from circulating progenitors of patients with different forms of IT made it possible, not only to define the pathogenetic mechanisms of these disorders, but also to begin to decipher the sequence of molecular events that are required for effective platelet production. 10 Platelets formed by cultured Mks resemble blood platelets in terms of morphology and function, 8 and this originated the idea of using them for transfusion purposes. In principle, an amount of human MKs appropriate to the in vitro production of platelet concentrates might reasonably be obtained from CD34 + embryonic stem cells, CD34 + umbilical cord blood stem cells, and induced pluripotent stem cells.…”
mentioning
confidence: 99%
“…Thereafter, further technical innovation resulted in the availability of devices for Mk culture that mimic bone marrow in terms of 3-dimensional structure, cellular composition, extracellular matrix and blood supply. 8 In vitro culture of Mks made a big contribution to our understanding of the enigmatic biology of these cells. In brief, it has been shown that Mks originating from Figure 1.…”
mentioning
confidence: 99%